Prosocial employee behavior: The dynamics of purpose, public accountability and hypocrisy - Clegg, S.; Pina e Cunha, M.; Rego, A.; Banerjee, B.; Abrantes, A. C. M. (Scandinavian Journal of Management)
Tensions can exist between organizational deeds and narratives of purpose. Employees who perceive such inconsistencies may go public with the aim of fostering internal organizational change oriented towards aligning rhetoric and reality. In doing so, they engage in a distinct form of prosocial behavior not yet fully examined in existing literature: societal-oriented prosocial behavior (SOPB) This behavior may be initiated through multiple motivational pathways – identification-repair, moral conviction, hypocrisy-aversion, or strategic calculation – all sharing four defining attributes: (1) employees adopting an external, public stance on (2), a societal-relevant issue with the aim of (3), promoting internal organizational change aligning organizational actions that are consistent with prior statements of purpose, thereby (4) signaling both their allegiance to and dissent from organizational practice. This paper explores both the distinctiveness of these motivational pathways and the specific content of employee societal-oriented prosocial behaviors.